Mapping of sequences in the 5' region and 3' UTR of tomato ringspot virus RNA2 that facilitate cap-independent translation of reporter transcripts in vitro. - Dinesh Babu Paudel; Hélène Sanfaçon (PLoS ONE, 2021)
Tomato ringspot virus (ToRSV, genus Nepovirus, family Secoviridae, order Picornavirales) is a bipartite positive-strand RNA virus, with each RNA encoding one large polyprotein. ToRSV RNAs are linked to a 5'-viral genome-linked protein (VPg) and have a 3' polyA tail, suggesting a non-canonical cap-independent translation initiation mechanism. The 3' untranslated regions (UTRs) of RNA1 and RNA2 are unusually long (~1.5 kb) and share several large stretches of sequence identities. Several putative in-frame start codons are present in the 5' regions of the viral RNAs, which are also highly conserved between the two RNAs. Using reporter transcripts containing the 5' region and 3' UTR of the RNA2 of ToRSV Rasp1 isolate (ToRSV-Rasp1) and in vitro wheat germ extract translation assays, we provide evidence that translation initiates exclusively at the first AUG, in spite of a poor codon context. We also show that both the 5' region and 3' UTR of RNA2 are required for efficient cap-independent translation of these transcripts. We identify translation-enhancing elements in the 5' proximal coding region of the RNA2 polyprotein and in the RNA2 3' UTR. Cap-dependent translation of control reporter transcripts was inhibited when RNAs consisting of the RNA2 3' UTR were supplied in trans. Taken together, our results suggest the presence of a CITE in the ToRSV-Rasp1 RNA2 3' UTR that recruits one or several translation factors and facilitates efficient cap-independent translation together with the 5' region of the RNA. Non-overlapping deletion mutagenesis delineated the putative CITE to a 200 nts segment (nts 773-972) of the 1547 nt long 3' UTR. We conclude that the general mechanism of ToRSV RNA2 translation initiation is similar to that previously reported for the RNAs of blackcurrant reversion virus, another nepovirus. However, the position, sequence and predicted structures of the translation-enhancing elements differed between the two viruses.